The Effectiveness of Text-Based Instruction in The Javanese Language Through Communicative Integrative Approaches to Writing Skills - Tilova, Eshia Monica; Supriyanto, Teguh; Utomo, Udi (Journal of Primary Education)
This study aims to determine the effectiveness of text-based Javanese language learning (text-based instruction) through communicative integrative approaches to student writing skills. This research method is an experimental study with a quasi-experimental design. The population of this study was class V Public Elementary School Tambakaji 05, Ngaliyan District, Semarang City in 2018/2019 with a sample of 43 students. Data collection used in this study for students' writing skills was measured using a performance test method with an instrument in the form of a learning implementation plan (RPP) and a performance sheet. Student confidence is measured by the non-test method in the form of observation sheets and documentation. Analysis of data used an independent sample t-test. The results showed as follows: there was an increase of 9.76 points higher in students' writing skills using Javanese text-based learning through an integrative approach. Learning Javanese text-based (Text-Based Instruction) through a communicative integrative approach is more effective in improving students' writing skills. The conclusion of the research is the learning of text-based Javanese language (Text-Based Instruction) through communicative integrative approaches effective in enhancing students' writing skills. The Javanese text-based learning model (Text-Based Instruction) through communicative integrative approach can help students who have difficulty learning Javanese texts.